Occupational Safety and Health Model Affecting Worker Performance Using Structural Equation Modelling - Romadhoni, Firda Amalia Putri; Putra, I Nyoman Dita Pahang (Poltekkes Kemenkes Surabaya, 2025)
Construction is one of the industries with a high risk of occupational accidents, which can negatively impact worker performance. The high rate of workplace accidents in this sector makes the implementation of an effective Occupational Safety and Health (OSH) system crucial. Occupational safety and occupational health can be key factors in improving worker performance. This study aimed to identify the most significant OSH factors affecting worker performance in the context of construction projects. The methodology used in this study was data collection through a questionnaire designed to evaluate various aspects of OSH and worker performance using a Likert scale. Data were collected from 50 respondents involved in five high-rise construction projects in Surabaya. The research findings indicate that occupational health factors have a more significant impact compared to occupational safety factors. The analysis shows that improving occupational health programs, such as regular health check-ups and providing adequate facilities, can directly improve worker performance. These findings underscore the importance of construction companies integrating occupational health aspects into their OSH programs, not only to protect workers but also to improve the performance of construction project workers. This study provides new insights into understanding the relationship between OSH and worker performance, while also offers practical recommendations for the construction industry to create a safer occupational environment and improve worker performance more effectively.